Incidentally detected testicular lesions <10 mm in diameter: can orchidectomy be avoided? - Scandura, G; Verrill, C; Protheroe, A; Joseph, J; Ansell, W; Sahdev, A; Shamash, J; Berney, D (Wiley, 2017)
Objective: To investigate the pathology of excised testicular lesions <10 mm in size. Patients and Methods: The pathological reports of 2 681 patients with testicular lesions from Barts Health NHS Trust and Oxford University Hospitals NHS Foundation Trust were reviewed as part of a service evaluation audit from January 2003 to May 2016. Cases in which the lesion had a maximum diameter of <10 mm were selected. Clinical features were also accessed, where available, to examine patient demographics, prediagnostic levels of serum markers, ultrasonographic findings and clinical details. Results: A total of 81 patients with a lesion size <10 mm on histology were identified and, of these, 16 (20%) had a lesion diameter <5 mm. Of the 81 patients, 56 (69%) had benign lesions. Of 16 patients with a benign lesion <5 mm in diameter, 15 underwent orchidectomy and just one underwent partial orchidectomy. Preoperative tumour markers were available in 47/81 patients. None of the 16 malignant tumours in these 47 patients were associated with raised tumour markers, while seven of 31 remaining patients with benign lesions had raised α‐fetoprotein and lactate dehydrogenase levels. In total there were 25/81 malignant cases (31%), which were all germ cell tumours (GCTs): 15 seminomas (60%) and 10 non‐seminomatous GCTs (40%). Only one GCT had a diameter of <5 mm, and this was a regressed tumour within an 18‐mm area of granulomatous inflammation. Only one GCT relapsed: a clinical stage I, embryonal carcinoma of 6 mm in maximum diameter. The 56 ‘benign’ cases included 34 sex cord stromal tumours, including 23 Leydig cell tumours (41%), eight Sertoli cell tumours (14%) and three mixed sex cord stromal tumours (5%). None showed any malignant features. The remaining 22/56 lesions (40%) were lesions with no further follow‐up. Benign lesions seemed to be associated with a small diameter, and we found <5 mm to be the best threshold for predicting benign vs malignant lesions (P = 0.002). Conclusion: The majority of testicular lesions <10 mm, identified by radiology, were benign, although approxmiately one‐third were malignant. In the present study, 100% of lesions <5 mm in diameter were benign. Tumour markers appear to be unhelpful in the distinction of these small tumours. We suggest that regular ultrasound surveillance be more widely used for testicular lesions of this size. Testicular tumours now have a very high cure rate and changes in size of lesions may be monitored prospectively with minimal risk of increased morbidity. Patients who undergo an orchidectomy for lesions <5 mm are ‘victims of modern imaging technology’. If surgery is undertaken in lesions 5–10 mm, patients should be counselled that two‐thirds of cases are benign.